Medir a pobreza a partir da abordagem dos direitos e da teoria dos conjuntos difusos. Um caso piloto em Santiago de Chuco, Peru - González-Moreno, Juana-María (2024)
Poverty, in addition to being a multidimensional phenomenon, constitutes a violation of human rights, and this must be taken into account when measuring it. In this work we make a conceptual and methodological proposal for measuring poverty in which, starting from a comprehensive conceptualization of poverty in its three facets (monetary poverty, subjective poverty and existence poverty), and from the rights approach to establish its dimensions and indicators, we apply fuzzy set theory to its quantification. The results obtained in the specific population as a pilot case, Santiago de Chuco, in the Libertad Department, Peru, show that this methodology allows a broader capture of the poverty experienced, the degrees of families’ poverty, and a better identification of situations of vulnerability, compared to the poverty line method.